In vivo adenine base editing reverts C282Y and improves iron metabolism in hemochromatosis mice - Rovai, Alice; Chung, BoMee; Hu, Qingluan; Hook, Sebastian; Yuan, Qinggong; Kempf, Tibor; Schmidt, Florian; Grimm, Dirk; Talbot, Steven R.; Steinbrück, Lars; Götting, Jasper; Bohne, Jens; et al. (Nature Communications, 2022)
Hemochromatosis is one of the most common inherited metabolic diseases among white populations and predominantly originates from a homozygous C282Y mutation in the HFE gene. The G > A transition at position c.845 of the gene causes misfolding of the HFE protein, ultimately resulting in its absence at the cell membrane. Consequently, the lack of interaction with the transferrin receptors 1 and 2 leads to systemic iron overload. We screened potential gRNAs in a highly precise cell culture assay and applied an AAV8 split-vector expressing the adenine base editor ABE7.10 and our candidate gRNA in 129-Hfetm.1.1Nca mice. Here we show that a single injection of our therapeutic vector leads to a gene correction rate of >10% and improved iron metabolism in the liver. Our study presents a proof-of-concept for a targeted gene correction therapy for one of the most frequent hereditary diseases affecting humans.
Gesehen am 28.10.2022